Correlation of cervical sagittal alignment parameters on full-length spine radiographs compared with dedicated cervical radiographs. Issue 1 (December 2016) - Carreon, Leah; Smith, Casey; Dimar, John; Glassman, Steven
Abstract Background Radiographic parameters to evaluate the cervical spine in adult deformity using 36-inch films have been proposed. While 36-inch films are used to evaluate spinal deformity, dedicated cervical films are more commonly used to evaluate cervical spine pathology. The purpose of this study is to determine correlations between sagittal measures from a dedicated cervical spine radiographs and 36-inch spine radiographs. Methods Patients who had standing cervical and 36-inch radiographs within four weeks of each other were identified. On separate occasions, the following measures were determined: C0-C2, C0-C7, C1-C2 and C2-C7 sagittal Cobb angles; T1 slope; chin-brow-vertical angle (CBVA), C1-C7 sagittal vertical axis (SVA), C2-C7SVA, center of gravity-C7 sagittal vertical axis (COG-C7SVA). Paired t-tests and correlation analyses were done between parameters from the cervical and the 36-inch film. Results Radiographic measurements were collected on 40 patients (33 females and 7 males, mean age of 48.9 ± 14.5 years). All correlations were statistically significant atp < 0.001. C0-C2 Cobb had the strongest correlation (r = 0.81) and C2-C7 Cobb had the weakest (r=0.62). Among sagittal balance parameters, COG-C7SVA had the weakest correlation (r = 0.42) and C1-C7SVA (r = 0.64) and the C2-C7SVA (r = 0.65) had strong correlations. The T1 slope and the CBVA had correlation coefficients of 0.74 and 0.91, respectively. There was no statistically significant difference in measures taken from the cervical film and 36-inch film, except for the C0-C7 Cobb (p = 0.000) with a measurement difference of 7° and the T1 tilt (p = 0.000) with a measurement difference of 5°. Conclusion Except for COG-C7 SVA, strong correlations between most cervical spine parameters taken from a dedicated cervical film and those taken from a 36-inch film were seen. 36-inch radiographs provide a reasonable estimation of cervical sagittal spine parameters and may obviate the need for a dedicated cervical spine radiograph.